2003
DOI: 10.1002/app.11682
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the addition mode of cycloaliphatic diepoxide on the morphology and film properties of crosslinkable core‐shell latex

Abstract: Core-shell latexes (LAs) designed for crosslinking with cycloaliphatic diepoxide were synthesized. The core contained methyl methacrylate (MMA), butyl acrylate (BA), and 2-hydroxyethyl methacrylate, and the shell was prepared with MMA, BA, and methacrylic acid. The crosslinker was coemulsified with the monomer and added during the LA preparation or after the polymerization either as an emulsion or in an organic solvent. The morphology of the LA was studied with atomic force microscopy and transmission electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…11) showed much better solvent resistance and pencil and indentation hardness when crosslinked with melamine resin. The result was in agreement with a study previously reported by Teng et al, where the carboxylic acid groups acted as a barrier to polymer chains due to electrostatic repulsion, thus limiting the extent of polymer chain interdiffusion and lowering the mechanical properties [53]. Indentation using the ESP (Enhanced Stiffness Procedure) method was performed to determine the depth profile of the hardness and the elastic modulus of the OH-latex, CO 2 H-latex and ESP method shows that the hardness and elastic modulus increased with addition of acid catalyst which indicated higher crosslinking [54][55][56].…”
Section: Effectiveness Of Cup Catalyst In Curing Of Co 2 H -Latex Andsupporting
confidence: 94%
“…11) showed much better solvent resistance and pencil and indentation hardness when crosslinked with melamine resin. The result was in agreement with a study previously reported by Teng et al, where the carboxylic acid groups acted as a barrier to polymer chains due to electrostatic repulsion, thus limiting the extent of polymer chain interdiffusion and lowering the mechanical properties [53]. Indentation using the ESP (Enhanced Stiffness Procedure) method was performed to determine the depth profile of the hardness and the elastic modulus of the OH-latex, CO 2 H-latex and ESP method shows that the hardness and elastic modulus increased with addition of acid catalyst which indicated higher crosslinking [54][55][56].…”
Section: Effectiveness Of Cup Catalyst In Curing Of Co 2 H -Latex Andsupporting
confidence: 94%
“…Prior to fabricating BPEI/PAA multilayer-coated latex spheres, latex spheres were prepared by using seeded semicontinuous polymerization with methyl methacrylate (MMA), butyl acrylate (BA), and 2-hydroxyethyl methacrylate (HEMA) as monomers, applying the Optimax (Mettler Toledo) working station, as described in the previous work. , Briefly, seed latex beads were first synthesized through batch emulsion polymerization. After dissolution of 4.82 g of sodium dodecyl sulfate (SDS), 0.81 g of sodium bicarbonate, 112.60 g of MMA, and 48.10 g of BA (molar ratio MMA/BA = 3:1) in 300.00 g of DI water at 60 °C under nitrogen protection, polymerization was initiated by adding ammonium persulfate aqueous solution (0.81 g in 10.00 g of DI water) and heated to approximately 80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…As addition of ammonium persulfate is a heat-releasing process, temperature should be raised carefully to avoid overheating. HEMA-rich latex beads with 60 wt % HEMA were then synthesized using the as-prepared seeds according to the previous work. , Seed dispersion was prepared by mixing 13.14 g of seeds and 0.12 g of sodium bicarbonate in 155.00 g of DI water at 80 °C for 30 min. Monomer pre-emulsion for the shell was obtained by adding 20.18 g of MMA, 25.82 g of BA, and 69.00 g of HEMA into 115 mL of aqueous mixture of 0.46 g of sodium bicarbonate, 0.80 g of SDS, and 0.58 g of ammonium persulfate and stirred for 1 h. The monomer pre-emulsion was slowly fed into the reactor using a peristaltic pump for 3.7 h. After feeding was completed, the reactor temperature was raised to 90 °C for at least 1.5 h to ensure maximum conversion.…”
Section: Methodsmentioning
confidence: 99%
“…The IBMA grafted the linear portion of the acrylic polymer with the microgels upon heating the film, which resulted in a significant increase in the shear holding power. G. H. Teng et al [12] have reported Core-shell latexes (LAs) designed for cross-linking with cycloaliphatic diepoxide, which have a better mechanical properties.…”
Section: Introductionmentioning
confidence: 99%